Efektivitas Pendayagunaan Dana Zakat, Infaq dan Sedekah Melalui Program Pendidikan - Choiril Bariyah; Latifatur Rahmah; Nurul Iman; Faridatul Jannah; Desi Endang Maisuri (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2025)
This study investigates the effectiveness of the utilization of ZIS funds by LAZ Sidogiri Pamekasan Branch through the Education program. The research method used is qualitative descriptive with a field research approach. Primary data were collected through direct interviews with LAZ administrators and secondary from related literature. The results of the study show that LAZ Sidogiri not only collects and distributes ZIS funds, but also allocates these funds through various educational programs such as Education scholarships and others. This study provides an overview of how amil zakat such as LAZ Sidogiri Pamekasan Branch can be an agent of change in improving access and quality of education for underprivileged communities through the utilization of ZIS. The implication of this research is the importance of effective and transparent fund management in maximizing the positive impact of social programs, especially in the field of Education.